Tempo de cidade, lugar de escola: dimensões do ensino secundário no Gymnásio Mineiro de Uberlândia (1929-1950) - Gatti, Giseli Cristina do Vale (2010)
This study communicates results of investigation in the field of History of Education within the specific theme of History of School Institutions, whose object of focus was the Gymnásio Mineiro de Uberlândia (Minas Gerais Jr. High School of Uberlândia), in Uberlandia, Minas Gerais, Brazil in the period from 1929 (the time at which the institution was made a state school) to 1950 (the time at which the process of massification of secondary education began in the country). The problematic that inspires the present investigation refers to understanding the role exercised by the Gymnásio Mineiro de Uberlândia among its students and the surrounding community in the midst of a broader process of modernization that was being carried out in the city and in the country at least since the end of the 19th Century, to which are added the concrete activities of urbanization, creation of railroads, highways, public services and intense commercial activity, as well as the creation of school institutions, under the leadership of elements of civil society, of religious confessions and of the State. The study started from a general hypothesis that the school institution chosen for examination, the Gymnásio Mineiro de Uberlândia, through the centrality, though not exclusivity, that it occupied in the educational formation of youth in the city in the period from 1929 to 1950, contributed to the configuration of an idealized conception of modernization of the city and of the region, which passed through the school institution and, above all, through secondary education preparatory for higher education, furthermore fomenting the patriotism that was in accord with the national political conception of that time. For verification of the hypothesis, an intense collection and analysis of the bibliography and of diverse sources of historical evidence was made, including: pertinent bibliography (dissertations, books written by historians and authors of memoirs); articles that deal with the question of local and regional history; printed, handwritten and iconographic documentation existing in school archives, in the Municipal Public Archives, in the CDHIS/UFU, and in private archives; as well as the construction of documents by means of the gathering of oral testimonies from former school directors, teachers and students. The results obtained deal with: 1) theoretical-methodological reflections regarding research in the area of the History of School Institutions, through the use of the category of school culture; 2) understanding of the more general purposes demanded for national secondary education both by means of examination of legislation created in the period and by means of the main school institutions created and in operation on a national and state level; 3) comprehension of the modernization process of the city of Uberlandia, taking into account different aspects, centered on examination of the phenomenon of schooling, especially that carried out within the environment of the Gymnásio Mineiro de Uberlândia; 4) comprehension of the public that attended the school in the sense of seeking to understand the role of a school institution that simultaneously conferred social distinction and social ascent, as well as the teaching methodologies used, the forms of disciplinary control, the patriotic content disseminated, the school s characteristic as a center of social, cultural and sporting life and the actions themselves of teachers and students within the school environment.